Metabolic insights into hypoxia adaptation in adolescent athletes at different altitudes: a cross-sectional study - Sánchez, Carlos A. R.; Pardo-Rodriguez, Daniel; Mancera-Soto, Erica; León, Lizeth; Paulucio, Dailson; D’Alessandro, Angelo; Santos, Caleb G. M.; Cristancho, Edgar; Monnerat, Gustavo; Ramos-Caballero, Diana M.; Cala, Mónica P.; Pompeu, Fernando (Frontiers in Molecular Biosciences, 2025)
Athletes use hypoxic training methods to enhance their performance under altitude conditions. Comparative studies involving populations from low (500–2,000 m) and moderate (2,000–3,000 m) altitudes offer an opportunity to understand the mechanisms behind adaptations to hypoxia. The present study combined data from metabolomics analysis based on gas- and liquid-chromatography mass spectrometry (GC-MS and LC-MS) to compare plasma profiles from 80 adolescent athletes at moderate- or low altitudes. 161 metabolites were identified, including 84 elevated and 77 decreased in moderate-altitude adolescents compared to their low-altitude counterparts. Pathway analysis revealed that metabolites related to carbohydrates, amino acids, and lipid metabolism differed between groups. Lipid metabolism was significantly altered in moderate-altitude athletes, including pathways such as linolenic and linoleic acid, sphingolipid, and arachidonic acid, as well as processes involving the transfer of acetyl groups into mitochondria and fatty acid biosynthesis. Biomarker analysis looking for signatures of chronic adaptation to moderate altitude identified glycerol and 5-oxoproline metabolites amongst the variables with the strongest sensitivity and specificity. This study demonstrates differences in metabolic profiles between moderate- and low-altitude populations and highlights the potential of these differential metabolites and associated metabolic pathways to provide new insights into the mechanisms of adaptation to moderate altitude.